Unbound bilirubin measurements in term and late-preterm infants. (18th April 2022) - Hegyi, Thomas; Chefitz, Dalya; Weller, Alan; Huber, Andrew; Carayannopoulos, Mary; Kleinfeld, Alan
Abstract: Background: Hyperbilirubinemia occurs in over 80% of newborns, and severe bilirubin toxicity can lead to neurological dysfunction and death. Unbound bilirubin (Bf) levels predict the risk of neurodevelopmental handicap, although total serum bilirubin (TSB) is used to manage care. Objective: To measure Bf levels in healthy infants, its relationship to TSB, and its response to phototherapy. We hypothesize unexpectedly high Bf levels, poor correlation with TSB and unpredictable response to phototherapy. Design/methods: Healthy infants were studied with simultaneous TSB and Bf measurements. The clinical data recorded included ethnicity, gender, birth weight, gestational age, and mode of delivery, Apgar scores, breast/formula feeds, and phototherapy. Results: One hundred thirty-two infants (3248.9 ± 509.2g, GA 38.7 ± 1.4 weeks), at mean age of the initial sample of 28.5 ± 15.6 h, had a TSB of 7.9 ± 2.7 mg/dl, and a Bf of 5.2 ± 3.2 nM. The correlation between Bf and TSB was significant but not between Bf and TSB for TSB >12 mg/dl. Bf >11nm were in 22.7% and >17 nM in 3.8% of infants. Post-phototherapy TSB and Bf levels were similar to those before treatment. Conclusions: The relationship between TSB and Bf in healthy infants is complex, with the inability of one to predict the other's level in infants with elevated TSB. The mechanism of bilirubin-related neurotoxicity suggests that the management of jaundice in healthy infants requires Bf measurements. Management of jaundice with TSB may result in more infants exposed to phototherapy. However, unexpected elevations of Bf occur in an apparently healthy population.